Pengaruh Pendidikan, Pengalaman Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Hotel Champlung Mas Resort & Spa Legian - Ni Luh Metri Lestari; Anak Agung Media Martadiani (Universitas Warmadewa, 2021)
In an effort to improve employee performance, high work experience education and work motivation are expected to be able to improve the quality of service to guests. The purpose of this study was to determine and analyze the effect of education, work experience and work motivation on employee performance at Hotel Champlung Mas Resort & Spa Legian. In this study, the employees used as a sample were 52 people. The data analysis technique consisted of validity test, reliability test, classical assumption test, multiple linear regression analysis, F test, and t test. The results of the analysis show that the effect of education on employee performance is obtained tcount (3.949)> ttable (2.010) with a significance level of 0.000 <i0.05, which means that the education variable has a significant positive effect on employee performance at Hotel Champlung Mas Resort & Spa Legian. The effect of work experience on employee performance is obtained tcount (2.271)> t table (2.010) with a significance level of 0.028 <0.05, which means that the work experience variable has a significant positive effect on employee performance at Hotel Champlung Mas Resort & Spa Legian. The influence of work motivation on employee performance is obtained tcount (4.026)> ttable (2.010) with a significance level of 0.000 <0.05, which means that the work motivation variable has a significant positive effect on employee performance at Hotel Champlung Mas Resort & Spa Legian. Based on the F test (simultaneously) obtained Fcount (17.384)> Ftable (2.79) with a significance value of F is 0.000 <0.05. This means that the variables education, work experience and work motivation simultaneously have a significant effect on employee performance at Hotel Champlung Mas Resort & Spa Legian with a value of R2 = 52.1% which means that 52.1% of employee performance at Hotel Champlung Mas Resort. & Spa Legian is influenced by the variables of education, work experience and work motivation while the remaining 47.9% is influenced by other variables not examined in this study.